Experiences of the legal system and impact on victims of sexual violence - Hildur Hálfdánardóttir 1995- (2024)
Sexual violence (SV) is a global health problem and can have significant impact on victims’ well-being. Despite the high prevalence of SV, reporting rates to the police remain low. Victims’ motivation to refrain from reporting is the desire to protect their emotional well-being. Victims that have gone to court with their case often report negative experiences on their journey to seek justice. This mixed-method study delved into the courtroom experiences of female victims of SV (n=11) that have been through the court system with their case. Recruitment was carried out through advertisements in Reykjavík University, social media, and organizations aiding victims of SV. The aim was to gather an understanding of the challenges that victims face and the impact on their well-being. The quantitative findings revealed participants’ disappointment with the legal system. They perceived the trial was unfair, while opinions on the fairness of the legal staff varied. The qualitative findings included four themes; “Of course it is many days of fear”, “I felt like I was going to pass out”, “You are just small and broken”, and “Then it is just a trauma”. Participants’ experiences with the legal system were predominantly negative, marked by varying degrees of preparation and uncertainty. Within an adversarial environment, they faced significant stressors, leading to heightened anxiety, fear, and sense of powerlessness, ultimately impacting their emotional well-being. The findings highlight the significance of providing comprehensive preparation and support to SV victims prior to their court appearances. We propose the use of virtual courtroom simulations as a preparatory tool to familiarize victims with the courtroom settings and develop coping strategies. By recognizing the challenges faced by victims in courtrooms and their impact on well-being, this study aims to contribute to the further development of supportive interventions for SV victims within the legal system. Keywords: Sexual violence, courtroom experiences, ...